Unemployement pattern - Zubairi, Ainol Madziah; Wan Husain, Wan Rohaida (Alumni and Career Service Division, IIUM, 2013)
The book presents the findings of the Ministry of Higher Education Tracer Study for the 2013 IIUM graduates. The TS2013 investigates the performance of IIUM graduates in the job market, their employability and employment status, as well as their evaluation of the general academic programmes and university facilities. For the year 2013, the study traced both the first-degree graduates and the post-graduates of the 29th convocation. A total fo 2093 graduates responded the questionnaires distributed before the convocation. Most of the respondents were Malaysians (83%) while 11.7% were international graduates from 53 different countries.